Effects of Thermo-Fatigue Loading, Hydrostatic Pressure, and Heat Aging on the Free-Volume and Crystalline Structure of Polypropylene-co-Ethylene Random Copolymer Pipes - Deveci, Suleyman; Oner, Mualla (WILEY-BLACKWELL, 2015)
Plastic pipes composed of polypropylene-co-ethylene random copolymers were subjected to accelerated aging by thermo-fatigue loading (i.e., thermal cycling using hot and cold water alternately under pressure), application of hydrostatic pressure at elevated temperatures, and heat aging in an oven. The effects of these accelerated aging techniques on the molecular and crystalline structure of the material were investigated using positron annihilation lifetime spectroscopy, Fourier-transform infrared spectroscopy, and differential scanning calorimetry. It was found that all three types of applied aging techniques decreased the size of the defects in the crystalline-amorphous interphase of the material, increased the density of these defects, and had a negligible impact on the free-volume hole size and intensity of the amorphous phase. Thermo-fatigue loading resulted in decreased lamellae thickness and lamellae thickness distribution; in contrast, hydrostatic pressure loading resulted in increased lamellae thickness and lamellae thickness distribution. The effect of thermo-fatigue loading on the chemical degradation of polypropylene was more pronounced than the effects of hydrostatic pressure and heat aging. POLYM. ENG. SCI., 55:641-650, 2015. (c) 2014 Society of Plastics Engineers
Keywords: ANNIHILATION LIFETIME SPECTROSCOPY; DIFFERENTIAL SCANNING CALORIMETRY; ISOTACTIC POLYPROPYLENE; POSITRON-ANNIHILATION; MECHANICAL-PROPERTIES; GLASS-TRANSITION; X-RAY; DEGRADATION; IRRADIATION; POLYETHYLENE; Engineering; Polymer Science